Regional and total body bone mineral density in elite collegiate male swimmers - Taaffe, D. R.; Marcus, R. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: To examine the role of long-term swimming exercise on regional and total body bone mineral density (BMD) in men. METHODS: Experimental design: Cross-sectional. Setting: Musculoskeletal research laboratory at a medical center. Participants: We compared elite collegiate swimmers (n = 11) to age-, weight-, and height-matched non-athletic controls (n = 11). MEASURES: BMD (g/cm2) of the lumbar spine (L2-4), proximal femur (femoral neck, trochanter, Ward's triangle), total body and various subregions of the total body, as well as regional and total body fat and bone mineral-free lean mass (LM) was assessed by dual-energy X-ray absorptiometry (DXA, Hologic QDR 1000/W). RESULTS: Swimmers, who commenced training at 10.7 +/- 3.7 yrs (mean +/- SD) and trained for 24.7 +/- 4.2 hrs per week, had a greater amount of LM (p < 0.05), lower fat mass (p < 0.001) and percent body fat (9.5 vs 16.2%, p < 0.001) than controls. There was no significant difference between groups for regional or total body BMD. In stepwise multiple regression analysis, body weight was a consistent independent predictor of regional and total body BMD. CONCLUSIONS: These results suggest that long-term swimming is not an osteogenic mode of training in college-aged males. This supports our previous findings in young female swimmers who displayed no bone mass benefits despite long-standing athletic training.